I2011PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 BONJOL - Listika, Yelvina; Nilawasti, Nilawasti; Zulfaneti, Zulfaneti (STKIP PGRI Sumbar, 2014)
Â ABSTRACTThis research was carried out due to the studentâs low learning achievement in mathematics in class VIII of SMPN 3 Bonjol. This research was aimed at revealing whether the mathematics conceptual understanding of the studentâs taught by using TTW cooperative learning was better than that of studentâs taught by using conventional learning. This was an experimental research which used random toward the subject design. Based on the result of data analysis it was found that the two sample classes were normally distributed and homogenous. Furthermore, the result of t-test indicated that the value of tcalculated (7,23) was higher than ttable (1,67) in which Î± was 0,05. This result showed that the mathematics conceptual understanding of the students taught by using TTW cooperative learning was better than that of studentâs taught by using conventional learning in class VIII SMPN 3 Bonjol registered in academic year 2013/2014.Â